2020
DOI: 10.1177/0300060520948758
|View full text |Cite
|
Sign up to set email alerts
|

Negative emotions and their management in Chinese convalescent cervical cancer patients: a qualitative study

Abstract: Objective The aim of the study was to understand the experience of negative emotions and coping styles of patients with cervical cancer during the rehabilitation period. Methods A descriptive qualitative research method was used. Purposive sampling was used to recruit participants. Semi-structured interviews were conducted with 18 cervical cancer patients and the data were analysed using content analysis. Results The analysis identified three relevant themes. Theme 1: Negative emotions in convalescent cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…Adopting positive coping styles decreased FCR levels in patients, while negative coping styles increased these levels, consistent with Blom et al [32]. It was previously observed [33] that adopting an upbeat coping style increased patient confidence during disease treatments, while adopting a negative coping style increased negative emotions and aggravated FCR levels. Park et al [34] showed that cognitive behavioral therapy based on positive thinking improved psychological distress, increased positive coping, and reduced FCR levels in patients.…”
Section: Response Modalitiessupporting
confidence: 87%
“…Adopting positive coping styles decreased FCR levels in patients, while negative coping styles increased these levels, consistent with Blom et al [32]. It was previously observed [33] that adopting an upbeat coping style increased patient confidence during disease treatments, while adopting a negative coping style increased negative emotions and aggravated FCR levels. Park et al [34] showed that cognitive behavioral therapy based on positive thinking improved psychological distress, increased positive coping, and reduced FCR levels in patients.…”
Section: Response Modalitiessupporting
confidence: 87%
“…Adopting positive coping styles decreased FCR levels in patients, while negative coping styles increased these levels, consistent with Blom et al [32]. It was previously observed [33] that adopting an upbeat coping style increased patient con dence during disease treatments, while adopting a negative coping style increased negative emotions and aggravated FCR levels. Park et al [34] showed that cognitive behavioral therapy based on positive thinking improved psychological distress, increased positive coping, and reduced FCR levels in patients.…”
Section: Response Modalitiessupporting
confidence: 87%
“…Ji et al [33] conducted a qualitative study to determine the negative moods and coping styles experienced by patients with cervical cancer during the rehabilitation period, and it was found that the negative emotions observed in the period until they regained their former health after cancer diagnosis and treatment consisted of FCR, concerns about gender perception, and feelings of inferiority due to deterioration in body image. During this period, patients thought that their current health information was insufficient and stated that they needed a strong rehabilitation.…”
Section: Factors Influencing Formentioning
confidence: 99%
“…Social support resources can prevent the occurrence of stressful life events; when stressful life events occur, they can change the way the event is perceived alleviate the stressful effect of the event and positively affect the adaptation of the person [25]. It is stated that one of the underlying reasons for the FCR is that cancer affects patients' relationships [24,33], one of their biggest fears is worrying about what will happen to their families, and social relationships and social support are important factors affecting FCR [23,30]. Family is the most used social support group to cope with FCR, and patients with high social support have lower FCR levels [25,34,36,38].…”
Section: Relationship Between Sociodemographic Characteristics and Fcrmentioning
confidence: 99%
See 1 more Smart Citation